Regional Amphora Standardization in Roman Africa (146 B.C.–A.D. 699+). - (:unkn) unknown (My University, 2023)
The present contribution aims to describe African amphora production between the late Republican age and Late Antiquity to show both how the African amphora underwent a long succession of standardization and diversification during the centuries and to reflect upon the different periods and regions where the standardized forms appear and develop. The paper is focused on three main research issues: the introduction of the Greco-Roman model in Africa and the first efforts at standardization, the development of different patterns of amphora production in different regions and its impact on the amphora shape, and the last transformations of typology, capacity, and production centers of the late Roman, Vandal, and Byzantine periods. Lastly, the paper compares the chrono-typological data of amphora production with the general chronology of Africa from the mid-2nd century B.C. to the end of the 7th century A.D.
Keywords: African Research